Accuracy of a Rapid Diagnostic Test for the Presence of Direct Oral Factor Xa or Thrombin Inhibitors in Urine—A Multicenter Trial - Harenberg, Job; Beyer-Westendorf, Jan; Crowther, Mark; Douxfils, Jonathan; Elalamy, Ismail; Verhamme, Peter; Bauersachs, Rupert; Hetjens, Svetlana; Weiss, Christel; Working Group Members; Ahrens, Ingo; Bömicke, Timo; Bauersachs, Rupert; Herold, Jörg; Beyer-Westendorf, Jan; Marten, Sandra; Naue, Christiane; Darius, Harald; Reill, Lorenz; Dürschmied, Daniel; Giesen, Roland; Olivier, Christoph; Grünewald, Martin; Klamroth, Robert; Kubicek-Hofmann, Cornelia; Orlovic, AnaMarija; Langer, Florian; Voigtländer, Minna; Lindhoff-Last, Edelgard; Zydek, Barbara; Menzel, Frank; Piper, Cornelia; Potratz, Isgandarova; Schellong, Sebastian; Müller, Carsten; Scholz, Ute; Krause, Michael; Sucker, Christoph; Trenk, Dietmar; Hromek, Julia; Leggewie, Stefan; Overhoff, Ulrich; Krämer, Fabian; Wolf, Ulrich (Thrombosis and Haemostasis, 2020)
The rapid determination of the presence of direct oral anticoagulants (DOACs) in a patient remains a major challenge in emergency medicine and for rapid medical treatment decisions. All DOACs are excreted into urine. A sensitive and specific point-of-care test has been developed to determine whether they are present in patient urine samples. This prospective multicenter study aimed to demonstrate at least 95% correct positive and negative predictive results for factor Xa and thrombin inhibitors in urine samples using DOAC Dipstick pads compared with liquid chromatography-tandem mass spectrometry (LC-MS/MS) (NCT03182829). Nine hundred and fourteen subjects were included and 880 were evaluated per protocol (factor Xa inhibitors apixaban, edoxaban, and rivaroxaban: n = 451, thrombin inhibitor dabigatran: n = 429) at 18 centers. The sensitivity, specificity, accuracy, and predictive values and agreement between methods for determination of factor Xa inhibitors were at least noninferior to 95% with a 0.5% margin and of thrombin inhibitor superior to 97.5%. These results were compared with LC-MS/MS results in the intention-to-analyze cohort (all p < 0.05). The receiver operating curve showed c-values of 0.989 (factor Xa inhibitors) and 0.995 (thrombin inhibitor). Visual evaluation of the factor Xa and thrombin inhibitor pads was not different between centers. Qualitative determination of both types of DOACs was accurate using the DOAC Dipstick compared with using LC-MS/MS. The high predictive values may impact laboratory and clinical decision-making processes.
Keywords: direct oral anticoagulants; point-of-care test; apixaban; edoxaban; rivaroxaban; dabigatran